Review of Arthur J. McDonald, A Progressive Voice in the Catholic Church in the United States: Association of Pittsburgh Priests, 1966-2019 - Jens Mueller (Journal of Moral Theology, 2020)
Review of Arthur J. McDonald, _A Progressive Voice in the Catholic Church in the United States: Association of Pittsburgh Priests, 1966-2019_